Modelling inflation rate volatility in Nigeria with structural breaks - Ismail O. Fasanya; Oluwasegun B. Adekoya (CBN Journal of Applied Statistics, 2017)
This study compares the performance of GARCH-Type models in modelling inflation volatility in Nigeria covering the period 1995M01 to 2016M10. In the paper, we provide two main innovations: (i) we analyze inflation rate of two pronounced consumer prices indices namely headline and core consumer price indices using the Augmented Dickey-Fuller break point test which allow for structural breaks in the data series; and (ii) the method is modified to include both symmetric and asymmetric volatility models. The empirical examination observes evidence of volatility persistence in the consumer price indices, but only headline is consistent with leverage effects. Thus, applying one-model-fits-all approach as well as discarding the role of structural breaks for inflation rate volatility in Nigeria will yield misleading and invalid policy prescriptions.
Keywords: C22; E31; 330; Inflation rate; Volatility modelling; Leverage effects; Monetary Policy